THE ROLE OF A SAFE EDUCATIONAL ENVIRONMENT IN THE FORMATION OF HEALTH-PRESERVING COMPETENCE OF STUDENTS (Physical Culture and Sport: Scientific Perspective, 2024)
The article examines the issues of the State's educational policy to ensure guarantees of the rights of students to achieve quality education under the condition of psychological and physical safety. It is shown that the comfort and safety of the educational environment of an educational institution is ensured by the unity of actions of all participants in the educational process.            It is analyzed that the issue of youth health is widely discussed around the world. It is considered that teachers do not stay aside from the problem of formation the foundations of a healthy lifestyle. The Law of Ukraine "On Education" proclaims "the priority of ... a human life and health" among the main principles of state policy in the field of education and establishes that an educational institution is responsible for the life and health of students during the educational process and creates conditions that guarantee the protection and strengthening of the health of students.The article defines a health-preserving educational environment as a set of managerial, organisational, educational and health-improving conditions aimed at the formation, strengthening and preserving the social, physical and mental health of students and teachers on the basis of psychological, pedagogical, medical and physiological means and methods of supporting the educational process, preventing risk factors, implementing a set of interdepartmental measures to create a socially adapted educational environment.It is emphasized that training of a future teacher for the development and creation a health-preserving educational environment in an educational institution involves provision conditions for the formation of their health-preserving competence on the basis of traditional and innovative technologies that ensure the preservation of students' health.            It is revealed that the integrated characteristic of a teacher's pedagogical activity covers not only his/her professional features, but also ensures the introduction of a healthy lifestyle, strengthening of the health of participants in the educational process and forms a value attitude to health and a healthy lifestyle. The developed health-preserving competence is a component of the structured system of professional competences of a teacher.
Keywords: students of the educational institutions; teachers; educational process; educational environment; safe educational environment; health-preserving educational environment; health-preserving competence